HIGH RESOLUTION IMAGING OF BORON DISTRIBUTION ON DIAMOND FILM USING ENERGY FILTERED TEM - A. Dimyati; S. Purwanto; R. Iskandar (Universitas Mercu Buana, 2016)
The main difficulty in investigation of thin film systems is the lack of capability to get detail information of the material in nano level due to the low resolution of conventional imaging techniques such as SEM, SIMS etc. In this work Electron Spectroscopy Imaging (ESI) in energy filtered transmission electron microscope (EFTEM) was used to produce a real image of boron distribution in a diamond film deposited on (111) Si by chemical vapor deposition. The result revealed the layer consists of 1.3 μm thick diamond structured carbon film adjacent to Si substrate and 120 nm amorph carbon layer on top most surface. Boron atoms were distributed uniformly in both layer, however slight higher concentration in the second layer is observed. There was obviously no grain boundary enrichment of Boron atoms observed.